2011
DOI: 10.1038/hr.2011.96
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of cardiovascular events and mortality among non-diabetic chronic kidney disease patients with hypertensive nephropathy: the Gonryo study

Abstract: To examine the clinical significance of hypertensive nephropathy (HN) among non-diabetic chronic kidney disease (CKD) patients. The study comprised 2692 CKD patients recruited from 11 outpatient nephrology clinics; these included 1306 patients with primary renal disease (PRD), 458 patients with HN, 283 patients with diabetic nephropathy (DN) and 645 patients with other nephropathies (ONs). All patients fulfilled the criteria of CKD, with a persistent low estimated glomerular filtration rate (eGFR) o60 ml min À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…12 In turn, coexistent hypertension is responsible for the progression of chronic kidney disease with accelerated segmental or global glomerulosclerosis that may be superimposed on the phenotype of the underlying kidney disease. 13,14 In this context, identification of genes and gene products that are linked to structural changes of the kidney remains one of the key questions in the analysis of renal impairment during hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…12 In turn, coexistent hypertension is responsible for the progression of chronic kidney disease with accelerated segmental or global glomerulosclerosis that may be superimposed on the phenotype of the underlying kidney disease. 13,14 In this context, identification of genes and gene products that are linked to structural changes of the kidney remains one of the key questions in the analysis of renal impairment during hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a prospective observational cohort study, named the Gonryo CKD Project, in an outpatient basis in 11 hospitals that offer nephrology services, including one university hospital in Miyagi Prefecture, located in the northeast area of Japan [14,15]. The participating hospitals covered almost the entire medical network of the area.…”
Section: Participantsmentioning
confidence: 99%
“…In the revision of the guidelines, the incidence of cardiovascular events and stroke was compared among the CHOIR and CREATE studies; the TREAT study, which was reported after the publication of the previous version of the guideline; the A21 study [42], which was an intervention study conducted in Japan; and the Gonryo study [48], which was an observational study conducted in Japan. As a result, the incidence of cardiovascular events was higher in Europe and the USA than in Japan.…”
Section: Statementmentioning
confidence: 99%